Comparison of Coronary Artery Bypass Grafting Outcomes in patients with and without Prior Percutaneous Coronary Artery Intervention : Coronary Artery Bypass Grafting Outcomes - Sikander Khan, Meenal; Ahmed, Haseeb; Shakil, Rafat; Jan, Azam; ul Islam, Mujahid; Khan, Bahauddin; Deedar Khan, Ahmad; Ahmad, Imtiaz; Ali Shah, Noor; Aman, Zarkesha (Pakistan Journal of Health Sciences, 2023)
Percutaneous coronary intervention (PCI) is a crucial treatment for patients with coronary artery disease (CAD), especially high-risk patients like advanced age, diabetes, chronic kidney disease, left main lesions, and multi vessel CAD. Objective: To compare coronary artery bypass grafting outcomes in patients with and without prior percutaneous coronary artery intervention. Methods: This retrospective 5-year cross-sectional study was conducted on 2579 patients operated for CABG in between August 1st, 2017, and December 31st, 2021 in a tertiary care hospital. All patients who underwent CABG were included in study, and comparison was done in patients with or without PCI. Data analysis were done by using SPSS version 23. p<0.05 was set statistically significant. Results: The results of perfusion and cross clamp time in operative room, use of IABP and reopening rates in both groups showed no statistically significant difference. The incidence of post-operative atrial fibrillation in group A is 4% Vs 1.5% in group B with significant p value of 0.028. Prolong ventilation, perioperative stroke and reintubation rates comparison in both groups were with non-significant p values. In hospital mortality was 4.5% in group A and 3.7% in group B with p-value of 0.370 which is non-significant. Conclusions: Patients with prior percutaneous coronary intervention can undergo CABG surgery with similar mortality rates as those with no prior PCI. The only significant difference in morbidity is post-operative risk of atrial fibrillation which is more in prior PCI patients’ group.